2020
DOI: 10.1017/s0025315420001010
|View full text |Cite
|
Sign up to set email alerts
|

Growth ofStegophiura nodosa(Echinodermata, Ophiuroidea) in the Pechora Sea

Abstract: The brittle star Stegophiura nodosa is one of the most abundant ophiuroid species living in Arctic seas and serves as a food resource for demersal fish. The study of autecological and biological patterns of S. nodosa is important for understanding the species reaction to environmental change. The growth features and growth rate of this brittle star from the Pechora Sea were estimated using the Gompertz equation as the basic mathematical model and compared with Bertalanffy equation parameters. Individual age wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…davidi were compared among different substrates using sigmoid growth functions. These models have become popular in recent decades and have been successfully applied to other crustacean species (Aragón‐Noriega, 2017), ophiuroidea (Stratanenko & Denisenko, 2020), fish (Hart & Chute, 2009; Kielbassa et al, 2010; Wang & Ma, 2016), birds (Brunner et al, 2021; Svagelj et al, 2019), mammals (Thorley & Clutton‐Brock, 2019) and even in plants (Ukalska & Jastrzębowski, 2019). Here, it was found that N .…”
Section: Discussionmentioning
confidence: 99%
“…davidi were compared among different substrates using sigmoid growth functions. These models have become popular in recent decades and have been successfully applied to other crustacean species (Aragón‐Noriega, 2017), ophiuroidea (Stratanenko & Denisenko, 2020), fish (Hart & Chute, 2009; Kielbassa et al, 2010; Wang & Ma, 2016), birds (Brunner et al, 2021; Svagelj et al, 2019), mammals (Thorley & Clutton‐Brock, 2019) and even in plants (Ukalska & Jastrzębowski, 2019). Here, it was found that N .…”
Section: Discussionmentioning
confidence: 99%